Authority in the Context of the Intergenerational Relations - Vališová, Alena (Wydawnictwo Naukowe UAM, 2013)
This article will concern a definition of the term “authority”, the meaning of the above competence in pedagogical interaction and also the possibility of how to develop social abilities and skills of teachers-engineers. As formulated in the terminology of activities, university teachers should possess expert, research, pedagogical and managerial competences. The development of authority (above all, of students and teachers in different types and levels of school) is the special area I have been paying close attention to (in theory and practice) for years.
Autorytet w kontekście relacji międzypokoleniowych
Keywords: authority; innovations of teaching; manipulation; social competences; teachers training; pedagogical interaction